EXPERIMENTAL STUDIES ON ENCEPHALITIS : I. TRANSMISSION OF ST. LOUIS AND KANSAS CITY ENCEPHALITIS TO MICE - Webster, Leslie T. (The Rockefeller University Press, 1935)
1. Mice of special strains injected intracerebrally with a 10 per cent emulsion of bacteria-free brain tissue from fatal cases of encephalitis in St. Louis and Kansas City develop a characteristic and fatal encephalitis. 2. Transmission of the disease can be continued indefinitely by injecting the bacteria-free brain tissue from the infected mice into healthy mice. 3. In the injected mice there is a 3 to 4 day incubation period, followed by hyperesthesia, coarse tremors, convulsions, prostration, and death in from 4 to 6 days. 4. The lesions in the mice with experimental encephalitis consist chiefly of perivascular accumulations of mononuclear leucocytes throughout the brain, stem, cord, and the pia, and destruction of pyramidal cells in the lobus piriformis and cornu Ammonis. 5. The human encephalitis brain tissue preserved in glycerine from the time of death of the patient apparently loses its infectivity for mice in about 32 days.